Singapore’s Event Exclusivity Strategy in ASEAN: Aggregating Regional Demand in the Digital Economy - Rahayu, Fryda Mutia; Narendra, Zezka Meva; Fadilah, Ai; Arliza, Arliza; Putri, Sylvia Octa; Adibowo, Rino (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This paper examines Singapore’s use of exclusivity of international concerts to aggregate regional economic demand in the ASEAN digital economy through a qualitative descriptive analysis of secondary data thematically analysed using concepts of platform economy and network effects. The results suggest that exclusivity is a deliberate means of aggregating cross-border demand and creating spillovers in events-related industries like tourism and digital transactions, enabling Singapore to act as both an event host and a platform hub that controls regional event circulation. Event exclusivity is found to be a form of event-led economic aggregation that enhances network centrality and lock-in, resulting in uneven economic development in ASEAN, while event-based economic gatekeeping is also introduced as a new dimension of digital political economy.